Thermo-mechanical properties of ABS/stainless steel composite using FDM - Mogan, J.; Sandanamsamy, L.; Wan Sharuzi, Wan Harun; Ismayuzri, Ishak; F. R. M., Romlay; K., Kadirgama; D., Ramasamy (Elsevier Ltd, 2024)
Fused deposition modelling (FDM) process is the most common and traditional additive manufacturing methods for producing complicated three-dimensional (3D) samples from computer-aided design data at a cheaper cost than alternative methods. However, when compared to other common plastic production processes, such as injection moulding, FDM produced parts results in low mechanical properties. Hence, the objective of this study is to produce composite filament using stainless steel (SS) as filler material to enhance the mechanical properties of ABS. ABS is a petroleum based thermoplastic that commonly used in FDM. The production of metal/polymer composites utilising ABS as the matrix and varied SS powder compositions was studied in this work. ABS/SS composite filaments containing 5, 10 wt% SS powder were developed in this experiment to compare with pure ABS for the FDM process. The result shows that the higher the composition of SS powder the lower the ultimate tensile strength and yield strength where 10 wt% SS shows 38.42 MPa in ultimate tensile strength while for yield strength it shows 24.32 MPa. Meanwhile, 10 wt% SS filament has better elongation which is 18.28 % compare to pure ABS that is 9.89 % and 13.3 % for 5 wt% SS. Thus, the percentage of filler plays an important role in determining the properties of ABS.